Challenges to multiple sclerosis care in Pakistan - Haris Majid Rajput; Mohammad Wasay (Journal of the Pakistan Medical Association, 2023)
Multiple sclerosis (MS) is the commonest cause of nontraumatic neurological disability in the young population.1 It is an immune mediated disorder affecting the central nervous system.2 Improvements in diagnostic modalities and formalization of diagnostic criteria have led to earlier and accurate diagnosis. Pakistan is amongst the low prevalence region for Multiple sclerosis.3 The estimated prevalence reported is at 10 per 100,000 persons to be suffering from MS.4 There is however increasing evidence that the south Asian region MS prevalence is underestimated, as reported in several studies from our neighbouring country Iran.